PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MELALUI METODE SIMULASI PRAKTIK DI MADRASAH IBTIDAIYAH (MI) AL ISLAM KELURAHAN CURUG KECAMATAN CIMANGGIS KOTA DEPOK - Lita Heni Kusumawardani; Etty Rekawati (Dinamika Journal : Pengabdian Masyarakat, 2019)
Clean and healthy living behaviors should be implemented early on as a starting point for the formation of healthy behaviors. The problem of lack of clean and healthy living behaviors was a major problem in school-aged children so that motivates writers to increase clean and healthy living behaviors. Clean and healthy living behaviors simulation was an interactive and innovative method of health education for school-aged children. The practice method used case study for four weeks. The activity was attended by 64 students by involving teachers and school health cadres.The results of the activities showed that the intervention of clean and healthy living behaviors simulation was able to increase the knowledge of school-age children from 49.3% to 64.5%, the attitude of school-age children increased from 41.8% to 58.7%, and school-age children's skills increased from 40.3% to 55.1%. Clean and healthy living behaviors simulation intervention can be used for nurses to develop promotive and preventive efforts in improving clean and healthy living behaviors among school-aged children. Keywords: clean and healthy living behaviors, practised simulation, school aged children